Convergent synthesis of the tetrasaccharide repeating unit of the O-antigen of Shigella boydii type 9 - Santra, Abhishek; Misra, Anup Kumar (Beilstein Journal of Organic Chemistry, 2011)
A convenient synthesis of the tetrasaccharide repeating unit of the O-antigen of Shigella boydii type 9 has been achieved in excellent yield using a [2 + 2] block glycosylation strategy. TEMPO-mediated selective oxidation of the primary alcohol of the tetrasaccharide derivative 8 to the carboxylic group followed by deprotection of the functional groups furnished target tetrasaccharide 1 as its 4-methoxyphenyl glycoside in high yield.
Keywords: diarrhea; glycosylation; O-antigen; oligosaccharide; Shigella boydii

(untitled) - von Seidlein, L.; Kim, D. R.; Ali, M.; Lee, H.; Wang, X.; Thiem, V. D.; Canh, D. G.; Chaicumpa, W.; Agtini, M. D.; Hossain, A.; Bhutta, Z. A.; Mason, C.; et al. (PLoS Med., 2006)

Shigella, Foodborne Bacterial Pathogens - Wachsmuth, K.; Morris, G. K. (Marcel Dekker Inc, 1989)

(untitled) - Gupta, A.; Polyak, C. S.; Bishop, R. D.; Sobel, J.; Mintz, E. D. (Clin. Infect. Dis., 2004)

(untitled) - Liu, B.; Knirel, Y. A.; Feng, L.; Perepelov, A. V.; Senchenkova, S. N.; Wang, Q.; Reeves, P. R.; Wang, L. (FEMS Microbiol. Rev., 2008)

(untitled) - Wathen-Grady, H. G.; Davis, B. R.; Morris, G. K. J. (Clin. Microbiol., 1985)

(untitled) - Reeves, P. R.; Wang, L. (Curr. Top. Microbiol. Immunol., 2002)

(untitled) - Knirel, Y. A.; Kochetkov, N. K. (Biochemistry (Moscow), 1994)

(untitled) - L’vov, V. L.; Musina, L. I.; Shashkov, A. S.; Ermakov, G. P.; Dmitriev, B. A. (Bioorg. Khim., 1987)

(untitled) - Kosek, M.; Yori, P. P.; Olortegui, M. P. (Curr. Opin. Infect. Dis., 2010)

(untitled) - Bhan, M. K.; Raj, P.; Srivastava, R.; Bhandari, N.; Kumar, R. (Indian Pediatr., 1988)

(untitled) - Klee, S. R.; Tzschaschel, B. D.; Singh, M.; Falt, I.; Lindberg, A. A.; Timmis, K. N.; Guzman, C. A. (Microb. Pathog., 1997)

(untitled) - Kweon, M.-N. (Curr. Opin. Infect. Dis., 2008)

(untitled) - Niyogi, S. K. J. (Microbiol., 2005)

(untitled) - Oaks, E. V.; Turbyfill, K. R. (Vaccine, 2006)

(untitled) - Pozsgay, V.; Kubler-Kielb, J. (ACS Symposium Ser., 2007)

(untitled) - Phalipon, A.; Costachel, C.; Grandjean, C.; Thuizat, A.; Guerreiro, C.; Tanguy, M.; Nato, F.; Vulliez-Le Normand, B.; Belot, F.; Wright, K.; Marcel-Peyre, V.; Sansonetti, P. J.; et al. (J. Immunol., 2006)

(untitled) - Pozsgay, V.; Coxon, B.; Glaudemans, C. P. J.; Schneerson, R.; Robbins, J. B. (Synlett, 2003)

(untitled) - Pozsgay, V. (Angew. Chem., Int. Ed., 1998)

(untitled) - Carlin, N. I.; Bundle, D. R.; Lindberg, A. A. (J. Immunol., 1987)

(untitled) - Santra, A.; Guchhait, G.; Misra, A. K. (Green Chem., 2011)

(untitled) - Panchadhayee, R.; Misra, A. K. (Synlett, 2010)

(untitled) - Madhusudan, S. K.; Agnihotri, G.; Negi, D. S.; Misra, A. K. (Carbohydr. Res., 2005)

(untitled) - Ludek, O. R.; Gu, W.; Gildersleeve, J. C. (Carbohydr. Res., 2010)

(untitled) - Du, Y.; Wei, G.; Cheng, S.; Hua, Y.; Linhardt, R. J. (Tetrahedron Lett., 2006)

(untitled) - Mukherjee, C.; Misra, A. K. (Synthesis, 2007)

(untitled) - Mukhopadhyay, B.; Collet, B.; Field, R. A. (Tetrahedron Lett., 2005)

(untitled) - Huang, L.; Teumelsan, N.; Huang, X. (Chem.–Eur. J., 2006)

(untitled) - Mukherjee, C.; Misra, A. K. (Glycoconjugate J., 2008)

(untitled) - Panchadhayee, R.; Misra, A. K. (Tetrahedron: Asymmetry, 2009)

(untitled) - Attolino, E.; Rising, T. W. D. F.; Heidecke, C. D.; Fairbanks, A. J. (Tetrahedron: Asymmetry, 2007)

(untitled) - Werz, D. B.; Seeberger, P. H. (Angew. Chem., Int. Ed., 2005)

(untitled) - Marmuse, L.; Nepogodiev, S. A.; Field, R. A. (Tetrahedron: Asymmetry, 2005)

(untitled) - Grundler, G.; Schmidt, R. R. (Liebigs Ann. Chem., 1984)

(untitled) - Sajtos, F.; Hajko, J.; Kover, K. E.; Liptak, A. (Carbohydr. Res., 2001)

(untitled) - Schmidt, R. R. (Angew. Chem., Int. Ed. Engl., 1986)

(untitled) - Bock, K.; Pedersen, C. (Acta Chem. Scand., Ser. B, 1975)

(untitled) - Duus, J. O.; Gotfredsen, C. H.; Bock, K. (Chem. Rev., 2000)

(untitled) - Crich, D.; Li, H. (J. Org. Chem., 2002)

(untitled) - Chakraborti, A. K.; Gulhane, R. (Chem. Commun., 2003)